Chin augmentation with cervical flaps associated with rhytidoplasty - Márcio Manoel Ferreira da Cunha (Revista Brasileira de Cirurgia Plástica, 2020)
Introduction: The lack of chin projection in the lower third of the face is sometimes responsible for the breaking of the facial contour harmony. Alloplastic implants, fillers, and osseous advancements have been used to correct these deformities. In this study, we propose a new maneuver to increase chin projection by using a cervical flap associated with rhytidoplasty. Methods: We assessed 11 patients who underwent operations using the cervical flap for chin projection between January 2017 and January 2018. The inclusion criteria were only patients who desired chin augmentation without the use of prosthetics, fillers, or osseous approaches, and those who would undergo rhytidoplasty. Results: A cephalometric analysis revealed improvements in chin projection and cervical contour, and no complications in the immediate or late postoperative period. Conclusion: In addition to presenting satisfactory results and acceptance, the cervical flap used for chin augmentation eliminated the use of synthetic materials, reduced surgical costs, and improved safety and durability, achieving a more refined mandibular contour and natural chin projection.